Plant microRNAs: Recent Advances and Future Challenges - Debat, Humberto Julio (2014)
MicroRNAs (miRNAs) are small ∼20–24 nt species of non-coding RNAs that modulate plant gene expression by means of gene silencing through sequence-specific inhibition of target mRNAs. MiRNAs derive from pol-II transcription of non-coding genes that are precisely processed in nuclear Dicing bodies by a microprocessor complex (dicer-like1–serrate–hyponastic leaves 1: DCL1-SE-HYL1), which recognizes stem-loop secondary-structure features of primary precursor miRNA transcripts (pri-miRNA). The proper processing of the pri-miRNAs results in a double-stranded small RNA that will eventually exit the nucleus and be loaded predominantly onto the effector complex Argonaute1 (Ago1). The single-stranded mature miRNA will guide AGO1, leading to cleavage or translational arrest of complementary mRNAs. MiRNA steady-state levels and activity are regulated not only by transcription rate of precursor transcripts, but also by direct degradation mediated by small RNA degrading nuclease1 (SDN1). miRNAs are retailored by 3′ editing through 2-O-methylation, uridylation and adenlylation, involving Hua enhancer1 (HEN1), HEN1 suppressor1 (HESO1) and probably the exosome—a phenomenon that has been elucidated only scarcely to date in Arabidopsis. MiRNA activity is involved not only in plant development, but also in signaling, abiotic stresses such as drought, heat and metal toxicity, pathogen interaction and symbiotic relationship regulation, among others. The engineering of miRNAs is paving the way to next-generation plant biotechnology by means of over-expression of natural miRNAs, generation of artificial microRNAs and inhibition of miRNA activity by target mimicry. This review highlights the importance of miRNAs in plant sciences by describing the latest updates in this research field.